Efficacy of the National Early Warning Score (NEWS) in Predicting In-Hospital Mortality in Surgical High Dependency Unit (HDU): A Prospective Study - Tariq, Ahmed; Khan, Shahid Mehmood; Hameed, Abdul; Ashraf, Chaudhary Imran; Maira Wajahat; Leghari, Muhammad Ajmal (Pakistan Armed Forces Medical Journal, 2025)
Objective: To assess efficacy of the National Early Warning Score in predicting in-hospital mortality in surgical High Dependency Unit. Study Design: Prospective longitudinal study. Place and Duration of Study: Surgical HDU, Department of Surgery, Combined Military Hospital, Rawalpindi Pakistan, from Jul to Dec 2023. Methodology: Patients admitted to surgical HDU were included by non-probability consecutive sampling. NEWS score was recorded for each patient within 24 hours of admission and classified into three triggering thresholds: low-risk (NEWS 1 to 4), medium-risk (NEWS 5 to 6) and high-risk (NEWS 7 or higher). Patients discharged within 3 days of admission, with missing NEWS variables and first NEWS recorded after 24 hours of admission were excluded. Demographic data and clinical characteristics were noted. Final outcome was recorded on 30th day after day of admission. Results: The study analyzed 350 patients admitted to surgical HDU, where 103(29.4%) patients died within 30 days after admission. Mortality was considerably higher in patients with high-risk threshold (92.1%) compared to medium-risk (54.9%) and low-risk (2.2%). High-risk NEWS threshold (≥7) at admission had sensitivity of 68% and specificity of 98% as a predictor of in-hospital mortality, AUC 0.945 (95% CI 0.916-0.974) with p-value<0.001, making it statistically significant. Patients with high-risk NEWS threshold on day of admission had less than 10% survival at 30 days. Conclusion: NEWS may be used as an objective scoring system to predict the risk of in-hospital mortality in surgical HDU settings.